2018
DOI: 10.13189/ujer.2018.060219
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Visualization Skills of 6th Grade Students

Abstract: Visualization is an effective method for students to internalize concepts and to establish correlations between concepts. Visualization method is especially more important in mathematics which is perceived as the combination of abstract concepts. In this study, whether 6th grade students can solve questions about 'Fractions' by using visual model and whether they can utilize visualization or not was searched. A literature scan about the visualization in teaching mathematics and an achievement test involving 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
2
8
0
2
Order By: Relevance
“…According to SP2, the visual question could innovate learning, provide inspiration, and make it more enthusiastic. This was consistent with the statement that using visualization to make students competent about a topic was very significant in bringing their interest to the lesson [6]. It showed SP2's interest in learning with the visual question.…”
supporting
confidence: 88%
See 4 more Smart Citations
“…According to SP2, the visual question could innovate learning, provide inspiration, and make it more enthusiastic. This was consistent with the statement that using visualization to make students competent about a topic was very significant in bringing their interest to the lesson [6]. It showed SP2's interest in learning with the visual question.…”
supporting
confidence: 88%
“…It showed that the former were more interesting than the latter. This was consistent with the statement that using visualization to make students competent about a topic was very significant in bringing their interest to the lesson [6].…”
supporting
confidence: 88%
See 3 more Smart Citations